POPULARITY AND POLITICS: THE UNCONVENTIONAL RISE OF BEN “COOTER” JONES IN THE AMERICAN SOUTH - Cooper, Kenneth J (Economics and Statistics Research Journal (ESRJ), 2023)
Celebrity politics is a growing area of research which explores the role of entertainment industry figures in American elections. This study looks specifically at Hollywood celebrities and their involvement in politics through ideological leanings in film production, public advocacy, and even running for major public offices. The convergence of entertainment and politics is notable as celebrities have advantages in fundraising, news coverage, and public recognition, which traditional candidates may not possess. However, concerns exist that celebrities lack the necessary governing skills to be effective public officials. This paper examines the case of Ben Jones, a celebrity who both won and lost elections, to understand the dynamics of celebrities in American politics. To explore this, a qualitative approach using case study analysis is employed. The findings suggest that while celebrities have advantages in campaigns, they may be overemphasized in terms of their potential impact on the political sphere. Thus, this study contributes to the literature on celebrity politics by providing a nuanced understanding of the role of celebrities in American politics, highlighting their potential advantages and limitations